Pengembangan dan Pelatihan Pembukuan Sederhana Berbasis Kas Pada Kelompok Kurma â€œUkhuwah Datu Nusantaraâ€ Kecamatan Gangga - Khalid Abjadi; Thatok Asmony; Endar Pituringsih; Muhammad Alfi Satia Pratama; Fathiah Rahman (Jurnal Gema Ngabdi, 2026)
Training and mentoring activities on the preparation of simple cash-based financial reports and the development of innovations were carried out to support the "Ukhuwah Datu Nusantara" business group in Sambik Bangkol Village, Gangga District, North Lombok Regency. The purpose of this activity was to contribute knowledge and skills to business group members regarding a simple cash-based financial recording system that can be applied in managing their businesses. This training aims to improve the business group's ability to create effective and accurate financial reports, thereby assisting in business planning and decision-making. In addition, this activity also provided new insights regarding the development of innovations to increase the competitiveness of business groups in utilizing local potential, such as the cultivation of dates and Sacha Inchi nuts. The implementation of the activity was carried out through an approach of lectures, tutorials, and discussions relevant to the needs of the business group. With this method, it is hoped that the business group will be able to carry out correct cash-based recording and bookkeeping, and manage their business more independently. This activity is expected to not only increase the income and welfare of business group members, but also strengthen the local agro-based economy in the region. Another hope of this activity is as a means of carrying out community service, especially in the areas of financial management and small business innovation.